Surgical Completion of Primarily Nonsurgical Stomatologic Operation Commenced Wearing Nonsterile Disposable Gloves - L. Dzan; P. Telekesová (Czech Dental Chamber, 2013)
Introduction, Aim: A dental practitioner may be exposed to a situation when simple tooth extraction (carried out wearing nonsterile disposable gloves) needs completing surgically due to unforeseen complications. This paper's objective is assessing the possible risk of pathogenic microorganism transfer if the operation is completed wearing the initially worn nonsterile disposable gloves. We suggested two hypotheses: H₀: Simple tooth extraction, converted to surgical tooth extraction due to unpredicted complications in the course of operation, may not be completed wearing the initially worn nonsterile disposable gloves for the reason of increased risk of nosocomial infection. H₁: Simple tooth extraction, converted to surgical tooth extraction due to unpredicted complications in the course of operation, may be completed wearing the initially worn nonsterile disposable gloves without having to worry about increased risk of nosocomial infection. Materials and Methods: 3000 talc-free nonsterile examination gloves from three different manufacturers were tested. They were latex gloves and nitrile gloves. 10 packs of gloves from each manufacturer, medium size, 100 units each, were tested while microbiological smears were carried out in a 1.5 class biohazard box to avoid airborne contamination of the material under examination. The smears were inoculated to blood agar (Bio-Rad, USA) and Schaedler agar (Bio-Rad, USA) and subsequently evaluated after incubation. Results and Statistics: A conventional statistical hypothesis test method on the binomial parameter distribution against a monomial alternative was applied to process the results for obligatorily pathogenic microorganisms. It was established in advance that hypothesis H₀: p ≥ 0,001 against alternative H₁: p < 0,001 on significance level α = 0,05 would be tested. Since the number of gloves with pathogenic microbiological finding (y) equalled 0, H₀ has been dismissed and H₁ has been favoured as the p value in this test equals p (y ≤ 0) = 0,9993000 = 0,0497 Discussion and Conclusion: Research data available suggest that no one has carried out microbiological testing of such a large number of nonsterile disposable examination gloves from three different manufacturers before. Since no obligatorily pathogenic microorganisms were found on the gloves (while opportune pathogenic microorganisms were statistically present at under 1 percent), simple tooth extraction in progress, subsequently converted to surgical tooth extraction, may be safely completed wearing them, not having to worry about nosocomial infection.